Post crisis banking sector regulation and European Union economic growth nexus - Ivica Klinac; Roberto Ercegovac; Mario Pečarić (Economic Review: Journal of Economics and Business, 2021)
The objective of this paper is to examine the impact of the new banking regulation on the European Union real economic activity in the period following the global financial crisis using a sample of 22 listed banking groups with high systemic importance, using dynamic panel models with a one-step GMM estimator. Higher regulatory capital and liquidity requirements are the main consequences of the global financial crisis, the pro-cyclical contraction of bank credit, and the advanced adaptive consolidation of the banking sector. The strengthened role of the ECB as lender of last resort and market maker may have had a significant impact on eliminating interbank market dysfunctionality and maintaining overall financial stability. In implementing the Basel III regulatory framework banks significantly increased the quality and consistency of the capital structure. On the other hand, the long-term stability of reduced systemic risks and the stimulation of the credit cycle are at stake. The research results clearly show that the necessary increase in a banking firm's regulatory capital and liquidity position have positive effects on real economic activity and potential sustainable economic growth.
Keywords: C33; D53; F65; G21; 330; regulatory requirements; bankcapital; bank liquidity; financial system; dynamic panel models